2009
DOI: 10.4067/s0718-19572009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de bacterias marinas cultivables de la ciudad costera Comodoro Rivadavia, Argentina

Abstract: This study identifies marine bacteria obtained from three sites along Comodoro Rivadavia coast, south of Argentina. Seawater and intertidal sediment samples were collected. Two of the sites were located close to the city sewage system (CR1, CR2) and the third one (CR3) was near from an oil buoy. Bacterial counts were performed on four culture media: BBR, BRN, mineral medium with crude oil and gas oil and ENDO for coliforms. The identification of bacteria was performed by using fatty acid methyl esters. The cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
1
4

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
0
1
4
Order By: Relevance
“…Cultivable heterotrophic microorganisms count were 2.7 9 10 5 CFU ml -1 . This value was greater to the CFU reported in the intertidal water contaminated with hydrocarbons (Pucci et al 2009), OBW from an oil company (Roy et al 2014) and hydrocarbon contaminated water (Youssef 2010), which were of the order of 10 2 to 10 4 CFU ml -1 . Youssef et al (2010) assigned the observed variations in the counts to the chemical nature of the samples.…”
Section: Obw Propertiescontrasting
confidence: 54%
“…Cultivable heterotrophic microorganisms count were 2.7 9 10 5 CFU ml -1 . This value was greater to the CFU reported in the intertidal water contaminated with hydrocarbons (Pucci et al 2009), OBW from an oil company (Roy et al 2014) and hydrocarbon contaminated water (Youssef 2010), which were of the order of 10 2 to 10 4 CFU ml -1 . Youssef et al (2010) assigned the observed variations in the counts to the chemical nature of the samples.…”
Section: Obw Propertiescontrasting
confidence: 54%
“…En los arrecifes de coralinos, las comunidades microbianas desempeñan un papel importante en la remineralización de los componentes orgánicos a inorgánicos, así como en la transferencia de energía a otros niveles tróficos (Henschke et al 2016;Kirchman, 2000;Pucci et al 2009). De hecho, algunos estudios informan que los microorganismos heterótrofos reciclan más de la mitad de la productividad neta en estos ecosistemas (Cho & Azam, 1990;Motegi et al 2013;Nelson et al 2011).…”
Section: Discussionunclassified
“…En los ecosistemas marinos, las bacterias heterótrofas constituyen un componente esencial en la trama trófica; estas, a través de su interacción con otros niveles, modifican los ambientes y controlan el reciclaje de nutrientes (Pucci et al 2009). Teniendo en cuenta el rol ecológico de las bacterias heterótrofas en el medio marino, actualmente es reconocida la posibilidad de utilizarlas como indicadoras microbiológicas para evaluar la calidad ambiental de los ecosistemas y la detección de condiciones ambientales desfavorables.…”
Section: Introductionunclassified
“…En cada caso se realizó un control, que contenía la muestra y la solución concentrada de nutrientes para conocer la mineralización en las muestras sin el agregado de hidrocarburos. Los sistemas se incubaron a 28 °C en oscuridad durante 50 días (Pucci et al 2009). …”
Section: Materials Y Métodosunclassified
“…La extracción de ácidos grasos se realizó sobre 40 mg de bacterias (peso húmedo) crecidas en la tercera estría de la placa de TSBA cultivada a 28 ºC durante 24 h, de acuerdo con el procedimiento del sistema de identificación (MIDI Newark, Del., USA www.midi-inc.com), según lo publicado anteriormente (Pucci et al 2009). …”
Section: Materials Y Métodosunclassified